1995
DOI: 10.1002/eji.1830250629
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency results in a priming environment conducive for Th1 cell development

Abstract: Certain infections, like that with the human immunodeficiency virus-1, deplete vitamin A, and when vitamin A levels are low, immune dysfunctions establish susceptibility to further infection. Our research has focused on the immune dysfunctions that are a consequence of vitamin A deficiency and that predispose to further infection. We previously studied a helminth infection in mice, and showed that when vitamin A levels are low, the immune response develops a strong regulatory T cell imbalance with excessive T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 46 publications
7
83
0
Order By: Relevance
“…Although no specific data are available for rexinoids, some older studies with various vitamin A derivatives and retinoids hint toward multiple alternative mechanisms. These mechanisms include the modulation of immune and inflammatory responses (34,35), changes in cytokineinduced responses in macrophages (36) and smooth muscle cells (37), and altered differentiation͞proliferation of macrophages (13,15) and smooth muscle cells (38). The expression of several permissive RXR heterodimers (including PPAR and LXR) in these immune-modulatory cells does not allow us to exclude an eventual contribution of the above mechanisms in the improvement in atherosclerosis in apoE Ϫ͞Ϫ mice.…”
Section: Resultsmentioning
confidence: 99%
“…Although no specific data are available for rexinoids, some older studies with various vitamin A derivatives and retinoids hint toward multiple alternative mechanisms. These mechanisms include the modulation of immune and inflammatory responses (34,35), changes in cytokineinduced responses in macrophages (36) and smooth muscle cells (37), and altered differentiation͞proliferation of macrophages (13,15) and smooth muscle cells (38). The expression of several permissive RXR heterodimers (including PPAR and LXR) in these immune-modulatory cells does not allow us to exclude an eventual contribution of the above mechanisms in the improvement in atherosclerosis in apoE Ϫ͞Ϫ mice.…”
Section: Resultsmentioning
confidence: 99%
“…The IL-4-deficient mice used in both studies were on the same genetic background (C57BL/6), and the parasites used (Puerto Rican strain) were from the same source, so we have no specific explanation for the apparent discrepancy. However, differences in the numbers of parasites used to infect our mice, diet (42), and housing conditions could affect disease progression during infection. Regardless, the data collected from the infected IL-10/IL-4-deficient mice support the deleterious role for highly polarized type 1 cytokine responses during infection with S. mansoni.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that vitamin A deficiency diminishes polyclonal and Ag-specific production of Th2 cytokines (6, 10), diminishes Th2-mediated Ab responses (4,8), increases Ag-specific production of IFN-␥ (10, 26), increases IL-12 production by unstimulated lymph node cells (9), and increases anti-viral (Th1-mediated) IgG2a responses (7). In addition, in vitro treatment with RA decreases production of IL-12 by APCs and IFN-␥ by T cells and NK cells (9,39). Conversely, supplemental vitamin A increases the IgA response and production of IL-5 and IL-10 while decreasing the IgG response and production of IFN-␥ (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A deficiency decreases the IgA, IgG1, and IgE responses but increases the IgG2a response to viral infection (6 -8). The underlying pattern of cytokine production by APCs and T cells is consistent with these effects on Ab production: vitamin A deficiency increases constitutive IL-12 production by macrophages (9), and during secondary in vitro stimulation of lymphocytes with Ag, vitamin A deficiency increases IFN-␥ production, but decreases IL-4 and IL-5 production (10). Conversely, supplemental treatment with vitamin A or retinoic acid (RA) 4 decreases IFN-␥ and increases IL-5, IL-10, and IL-4 production (11-13).…”
mentioning
confidence: 87%